(UN)EXPECTED TWISTS OF HYBRID IDENTITY AS MIRRORED IN THE EXAMPLE OF IQBAL BROTHERS IN THE NOVEL WHITE TEETH BY ZADIE SMITH (Živi jezici: Journal for Foreign Languages and Literatures, 2021)
Zadie Smith's first novel White teeth tells a story about twins Magid and Millat Iqbal. Born into a family of Bangladeshi migrants, from an early age the brothers are faced with a heavy burden of their parents' expectations, legacy, and the reality of contemporary Britain. This paper sets out to show how the hybrid identity of the twins will evolve in an expected way from the point of view of theory and conversely how it will be unexpected from the perspective of the novel's plot. Using text evidence contained in the novel as well as theories of significant thinkers from the sphere of colonial and postcolonial studies, this research aims to prove that the destiny of the twins was expected from the prism of theory, but unexpected if plot is taken into consideration. This paper suggests in conclusion that the twins represent two sides of postcolonial experience which complement and obliterate each other simultaneously. This research also aims to open the space for more studies conducted with a view to examining this novel and connecting it with most important works on hybrid identity from the area of colonial and postcolonial studies.
Keywords: White teeth; hybrid identity; Magid and Millat Iqbal; postcolonial subject; the expected and the unexpected